Inflammasomes cross-talk with lymphocytes to connect the innate and adaptive immune response - Hongliang Zhang; Jie Gao; Yujie Tang; Tengchuan Jin; Jinhui Tao (Journal of Advanced Research, 2023)
Background: Innate and adaptive immunity are two different parts of the immune system that have different characteristics and work together to provide immune protection. Inflammasomes are a major part of the innate immune system that are expressed widely in myeloid cells and are responsible for inflammatory responses. Recent studies have shown that inflammasomes are also expressed and activated in lymphocytes, especially in T and B cells, to regulate the adaptive immune response. Activation of inflammasomes is also under the control of lymphocytes. Therefore, we propose that inflammasomes act as a bridge and they provide crosstalk between the innate and adaptive immune systems to obtain a fine balance in immune responses. Aim of Review: This review systematially summarizes the interaction between inflammasomes and lymphocytes and describes the crosstalk between the innate and adaptive immune systems induced by inflammasomes, with the aim of providing new directions and important areas for further research. Key Scientific Concepts of Review: When considering the novel function of inflammasomes in various lymphocytes, attention should be given to the activity of specific inflammasomes in studies of lymphocyte function. Moreover, research on the function of various inflammasomes in lymphocytes will help advance knowledge on the mechanisms and treatment of various diseases, including autoimmune diseases and tumors. In addition, when studying inflammatory responses, inflammasomes in both lymphocytes and myeloid cells need to be considered.